2022
DOI: 10.3389/fchem.2022.1008884
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the preparation of ceramsite from petrochemical excess sludge

Abstract: Petrochemical excess sludge, as hazardous solid waste, poses a great threat to the environment and is difficult to dispose of in an economic and environmentally friendly way. A new alternative of using the petrochemical excess sludge to prepare ceramsite is proposed. The relationship between the sintering behavior of dried excess sludge, including the composition, temperature, fluxing agent, and pore-forming agent addition, and the properties of ceramsite is investigated. The properties of ceramsite are primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Liu et al [13] used the petrochemical sludge as raw material to prepare ceramsite and reported an optimal ratio of sludge 20 wt-%, clay 71 wt-%, and Fe 2 O 3 as pore-forming agent, sintered at 1200°C. The concentration of sintered products through leaching was in accordance with Chinese hazardous waste identification standards.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [13] used the petrochemical sludge as raw material to prepare ceramsite and reported an optimal ratio of sludge 20 wt-%, clay 71 wt-%, and Fe 2 O 3 as pore-forming agent, sintered at 1200°C. The concentration of sintered products through leaching was in accordance with Chinese hazardous waste identification standards.…”
Section: Introductionmentioning
confidence: 99%